Factors influencing multiple non-utilised healthcare appointments from patients’ and healthcare providers’ perspectives: a qualitative systematic review of the global literature - Asrar Aldadi; Kathryn A Robb; Andrea Williamson (BJGP Open)
Background: The term 'non-utilised appointments' emerged in 2019 but lacks a clear definition. We focus on multiple non-utilised appointments owing to recent advances in understanding 'missingness' in UK health care. Studies on missed appointments show conflicting results regarding interventions such as text messaging owing to oversight of occasional versus repeated missed appointments. Understanding patient and healthcare-related factors in multiple non-utilised appointments is crucial for improving interventions and patient engagement. Aim: To identify factors influencing multiple non-utilised appointments from patients' and healthcare providers' perspectives. Design & setting: A systematic review of qualitative research identifying factors that influence multiple non-utilised appointments across diverse global healthcare settings. Method: The review employed a qualitative systematic approach, encompassing diverse papers from multiple databases, irrespective of patient or healthcare provider age, location, or setting. Data analysis followed Thomas and Harden’s thematic synthesis method. Themes are presented in alignment with both the health service and patient perspective aspects of the Levesque access model. Results: Ten thousand and eighty-six records were retrieved. Five studies met the inclusion criteria and were analysed. Six key themes influenced appointment utilisation. Healthcare system determinants highlighted provider–patient relationship and professionalism, and healthcare organisation factors role in appointment utilisation. Patient experience and decision making explored personal factors. Additionally, communication, support, and engagement delved into challenges with communication and language, family and social support, and socio-familial barriers to appointment utilisation. Health and wellbeing factors encompassed medical conditions, mental and emotional factors, and psychosocial determinants affecting appointment utilisation. Moreover, financial constraints and socioeconomic factors were identified as significant contributors. Lastly, healthcare access and barriers addressed transportation challenges, accessibility issues, and geographical barriers impacting healthcare access. Conclusion: The analysis reveals complex factors influencing multiple non-utilised appointments. Strong provider–patient relationships improve care accessibility. Flexible scheduling and patient-centred approaches are pivotal, alongside addressing workplace discrimination. Tailored healthcare services and overcoming geographical barriers are essential. Ensuring safety, accessibility, and communication, while supporting vulnerable groups and mental health needs, are necessary. Equitable access to services and alternative transportation solutions are essential for comprehensive healthcare delivery.